Faktor yang Berpengaruh Terhadap Kualitas Audit Pada Inspektorat Pemerintah Kabupaten Badung - I Made Putra Dwi Antara; Ni Made Sunarsih; Ida Ayu Budhananda Munidewi (Juara: Jurnal Riset Akuntansi, 2022)
This study aims to determine the effect of Organizational Ethical Culture, Professionalism, Work Experience, Time Pressure and Locus of Control on Audit Quality at the Government Inspectorate of Badung Regency. The sample in this study were all auditors in the Government Inspectorate of Badung Regency, totaling 50 respondents. Determination of samples using saturated samples. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that the variables of organizational ethical culture, professionalism, work experience have a positive effect on audit quality and time pressure has a negative effect on audit quality, while Locus of Control has no effect on audit quality.